The Motivation of Indonesia in Doing Carbon Trading with Norway (2010-2016) - Muhammad Fachrie (Indonesian Journal of International Relations, 2017)
Abstract This research explains about the motivation of Indonesia in doing carbon trading with Norway. As a country which has tropical rainforest, Indonesia has become important for the developed countries in the carbon trade cooperation, especially Norway. Indonesia has the potential natural resources, such as tropic rainforest and large of land, that can be used to reduce carbon emissions in the world. By signing the letter of intent (LoI) on May 26th in 2010 in Oslo, Indonesia and Norway have agreed to conduct carbon trading both of these two countries. On the one hand, this cooperation can be advantageous for Indonesia, because Indonesia gets one billion US dollars from Norway for Reduced Emissions from Deforestation and Forest Degradation (REDD) program , but on the other hand Indonesia can not maximize the exploitation of forestry sector and land because of the limitation caused by REDD. It eventually causes the carbon trading between Indonesia and Norway becomes important to be inquired. Keywords: Environment, Carbon Trading, Priso Indone Policy Abstrak Penelitian ini menjelaskan tentang motivasi Indonesia dalam melakukan perdagangan karbon dengan Norwegia. Sebagai negara yang memiliki hutan hujan tropis, Indonesia menjadi penting bagi negara- negara maju dalam kerja sama perdagangan karbon, terutama Norwegia. Indonesia memiliki potensi sumber daya alam, seperti hutan hujan tropis dan lahan yang luas, yang dapat digunakan untuk mengurangi emisi karbon di dunia. Dengan menandatangani letter of intent (LoI) pada 26 Mei 2010 di Oslo, Indonesia dan Norwegia telah sepakat untuk melakukan perdagangan karbon kedua negara ini. Di satu sisi, kerjasama ini dapat menguntungkan bagi Indonesia, karena Indonesia mendapat satu miliar dolar AS dari Norwegia untuk program Pengurangan Emisi dari Deforestasi dan Degradasi Hutan (REDD), tetapi di sisi lain Indonesia tidak dapat memaksimalkan eksploitasi sektor kehutanan dan lahan karena keterbatasan yang disebabkan oleh REDD. Hal tersebut menyebabkan perdagangan karbon antara Indonesia dan Norwegia menjadi penting untuk dipertanyakan. Kata Kunci: Lingkungan, Perdagangan Karbon, Prisoner’s Dilemma, Pilihan Rasional, Kebijakan Luar Negeri Indonesia